Estudio de competencias genéricas y resultados de aprendizaje en estudiantes de cultura física - Consuelo Corali, Vega Jua (2022)
ABSTRACT This research aimed to analyze the study of generic competencies in the development of learning outcomes in students who graduated from Physical Culture in the academic periods April 2017 - September 2017, October 2017 - March 2018, October 2018 - March 2019, and April 2019 – September 2019. Knowing that generic competencies are the abilities, skills, knowledge, and abilities that students possess, which are reflected in the learning outcomes in professional life. Methodologically, the research has a qualitative approach with a nonexperimental design. Due to the type of research, it was essential, bibliographical with a cross-section. Due to the level, it was documentary and descriptive. The population was the students of the National University of Chimborazo of the Physical Culture career. In the same way, primary and secondary bibliographic sources were used in different scientific documents. The study variables were addressed, the same ones are annexed in Scielo, Redalyc, Scopus, Elsevier journal, and websites. The sample was the following academic periods April 2017 - September 2017, October 2017 - March 2018, October 2018 - March 2019, and April 2019 - September 2019. The technique used in the present investigation was the survey. The instrument was the graduate file, allowing the conclusion that necessities have been considered for each degree and each subject. The critical generic competencies for the professional profile are developed, clearly establishing the learning results that must be achieved by students at the end of their training. In any work environment, being an excellent professional implies possessing the scientific knowledge necessary for the job and social skills, adaptability skills, the ability to make decisions, communication skills, the ability to work as a team, etc.